Digital E-Assessment Technology in Assessing Students’ Tolerance Character - Asrial; Syahrial; Dwi Agus Kurniawan; Husni Sabil; Rahmat Perdana; Rizka Octavia Sandra; Muhammad Iqbal (Universitas Pendidikan Ganesha, 2022)
The existence of a digital-based assessment system will support the assessment of student character in the learning process. Character assessment using e-assessment will greatly assist teachers in overcoming paper wastage, streamlining time, overcoming large expenditures and making students more focused in filling out characters. This study aims to analyze the character of tolerance in elementary school students and to determine the feasibility of the product. This research is a development research using 4D development design. The sample of this study was 175 students. Quantitative data from this study were obtained from the validation of media experts and the results of the student tolerance character assessment, while qualitative data was obtained from interviews. The quantitative data in this study were analyzed using descriptive statistics and inferential statistics, while the qualitative data used Miles & Huberman analysis. The results of the descriptive analysis of the character assessment of student tolerance are in a good category, and there are differences in the character of student tolerance in the 3 schools. The results of the validation of media experts on the development of web-based assessment are in the good category so that the product can be used to assess the character of student tolerance. The implications of this research lie in time efficiency in processing and distributing data, saving procurement costs, and ease of use in assessing student character using web-based assessment.